PEMANFAATAN CHATGPT DALAM PENERJEMAHAN BAHASA ARAB PADA MAHASISWA PBA SEMESTER 7 UIN RADEN INTAN LAMPUNG - Mukti Parani, Ema Dwi; Lailatul Wahidah, Yeni; Ghazi, Fachrul; Damanhuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the use of ChatGPT as a translation-support tool for Arabic texts among seventh-semester students of the Arabic Language Education Program at UIN Raden Intan Lampung. The research is motivated by the increasing integration of artificial intelligence in language learning and the growing tendency of students to rely on AI-based translation tools when dealing with academic Arabic texts. This study aims to (1) describe how ChatGPT is utilized in the translation process, (2) analyze the semantic quality of ChatGPT’s translation output by comparing it with the original meaning of selected mahfudzat texts “ الشَّرَفُ بِالْأَدَبِ”, and identify the benefits and challenges of its use. Employing a descriptive qualitative method, data were collected through semi-structured interviews, observations, and documentation, and were analyzed using the Miles and Huberman model. The findings reveal that ChatGPT is used intensively to translate course materials, articles, qirā’ah texts, and examination items, as well as to understand vocabulary and sentence structure. The comparison of translation results indicates that ChatGPT generally produces accurate and readable outputs, although some segments include interpretative additions and structural inconsistencies that require manual verification. This study concludes that ChatGPT is effective as an initial comprehension tool in translation learning, yet it cannot replace the linguistic competence of human translators, particularly in academic and religious texts that demand contextual precision. These findings highlight the importance of AI literacy and critical verification skills in ensuring responsible and appropriate use of ChatGPT in translation practice.